2017
DOI: 10.1002/adma.201700616
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule Solar Cells with Simultaneously Enhanced Short‐Circuit Current and Fill Factor to Achieve 11% Efficiency

Abstract: High-efficiency small-molecule-based organic photovoltaics (SM-OPVs) using two electron donors (p-DTS(FBTTh ) and ZnP) with distinctively different absorption and structural features are reported. Such a combination works well and synergically improves device short-circuit current density (J ) to 17.99 mA cm and fill factor (FF) to 77.19%, yielding a milestone efficiency of 11%. To the best of our knowledge, this is the highest power conversion efficiency reported for SM-OPVs to date and the first time to comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 32 publications
0
72
0
Order By: Relevance
“…Mobility in chiral materials is known to be extremely sensitive to supramolecular organisation . Morphological analysis revealed that the asymmetric compound is the more inclined to form ordered crystalline domains when spun‐cast as a blend with PC 61 BM, which could be of interest for larger molecules based on similar materials with greater charge transport …”
Section: Discussionmentioning
confidence: 99%
“…Mobility in chiral materials is known to be extremely sensitive to supramolecular organisation . Morphological analysis revealed that the asymmetric compound is the more inclined to form ordered crystalline domains when spun‐cast as a blend with PC 61 BM, which could be of interest for larger molecules based on similar materials with greater charge transport …”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69] Although our current focus is mainly on the small molecules, conclusions made from this study are expected to be also applicable for the polymer OPVs. [67][68][69] Although our current focus is mainly on the small molecules, conclusions made from this study are expected to be also applicable for the polymer OPVs.…”
Section: Descriptors For Machine Learning Modelsmentioning
confidence: 94%
“…Encouragingly, the large-area (2.03 cm 2 ) flexible ITO-free NF OSC with doctor-blade printing exhibits a remarkable PCE of 7.6%, which is the highest PCE reported to date in large-area flexible ITO-free doctor-bladed NF OSCs. [33] A strong diffraction peak at 0.50 A −1 is seen in outof-plane direction, coming from other ITIC packing structure. [29] In comparison, a low PCE of 5.86% is obtained in the flexible ITO-free spin-coated OSC (consuming four times more solution than the blade-coated one), which illustrates great benefits of doctor-blade printing for low-cost NF OSC manufacturing.…”
Section: Bis[5-(2-ethylhexyl)-2-thienyl]mentioning
confidence: 97%